Identification of binding interactions between myeloperoxidase and its antibody using SERS - Papazoglou, E. S.; Babu, S.; Mohapatra, S.; Hansberry, D. R.; Patel, C. (Nano-Micro Letters, 2010)
Surface Enhanced Raman Spectroscopy (SERS) is a widely used spectroscopic method that can dramatically increase the sensitivity of Raman spectroscopy and has demonstrated significant benefit in the identification of biological molecules. We report the use of SERS in differentiating the bound immunocomplex of myeloperoxidase (MPO) and its antibody from the unbound complex and its individual components. The SERS signal was enabled by gold nanoparticles attached to MPO, pAb and their immunocomplex at an excitation wavelength of 785 nm. The obtained SERS spectrum of MPO is in agreement with previous literature. Comparative SERS spectrum analysis of MPO, pAb, and their immunocomplex reveals the significant peak shifts and intensity variations caused by the conformational changes due to the immunocomplex formation. Several key areas have been identified which correspond to specific amino acids being shielded from undergoing resonance while new amino acid residues are made visible in the SERS spectrum of the immunocomplex and could be a result of conformational binding. Our work demonstrates the capability of SERS to identify binding events and differentiate an immunocomplex from its unbound components with direct applications in biosensors.